Aortic thrombosis: the forgotten source of ischemic stroke. A case report and systematic review of the literature - Christian Basile (PAGEPress Publications, 2021)
Ischemic stroke represents one of the most important health problems in industrialized countries, both for epidemiological and socio-economic impact. The presence of thrombi in the aorta is rare and its treatment has not been uniquely defined. Here we report the case of an 82-years-old man with aortic thrombosis and acute ischemic stroke.